Applying ergonomics to nurse computer workstations: review and recommendations. - Nielsen K; Trinkoff A (CIN: Computers, Informatics, Nursing)
Nursing is associated with high rates of musculoskeletal disorders from patient handling, and nurses are at high risk for developing cumulative trauma disorders, which can result from computer usage. Although there are many benefits to using computers in the workplace, nurses need to incorporate ergonomic factors into work settings to promote safe workplace environments. This article reviews recent literature about computer workstation ergonomics, discusses related policies, and makes recommendations about computer workstation design and related research in nursing workplace settings.